2019
DOI: 10.1352/1934-9556-57.6.485
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Parent Input in IEP Development Through Analysis IEP Documents

Abstract: Parent input in Individualized Education Program (IEP) development is the clear expectation in U.S. education law. Every IEP team must include parents, and their input must be equally considered when developing IEPs. The present study used content analysis of 88 IEPs of students with intellectual and developmental disabilities to explore team membership, concerns parents raised during IEP meetings, and evidence that parent concerns and priorities are reflected in IEP goals and supplementary aids and services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…In addition, Kurth and colleagues [27], who studied parents' input and power structures through 88 IEPs prepared for pupils with intellectual and developmental disabilities, revealed that parents' hopes and concerns recorded in the IEPs were formulated into goals or services only two-thirds of the time; see also [36]. The power structures could also be seen in their analysis of the wording of the IEPs, which implied that the IEP teams were composed of school personnel who gathered information about the families ("the IEP team has requested and considered the concerns of Parents(s)/Educational decision maker") [27] (p. 494). The current study adds to the previous research that, similar to parents of pupils without the AACM or PIMD, the participation of parents of pupils with the AACM or PIMD varies in the goal-setting process.…”
Section: Main Mediators' Collaborative Positionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Kurth and colleagues [27], who studied parents' input and power structures through 88 IEPs prepared for pupils with intellectual and developmental disabilities, revealed that parents' hopes and concerns recorded in the IEPs were formulated into goals or services only two-thirds of the time; see also [36]. The power structures could also be seen in their analysis of the wording of the IEPs, which implied that the IEP teams were composed of school personnel who gathered information about the families ("the IEP team has requested and considered the concerns of Parents(s)/Educational decision maker") [27] (p. 494). The current study adds to the previous research that, similar to parents of pupils without the AACM or PIMD, the participation of parents of pupils with the AACM or PIMD varies in the goal-setting process.…”
Section: Main Mediators' Collaborative Positionsmentioning
confidence: 99%
“…Previous research on parents' and pupils' participation in the IEP process, some of which involves pupils with intellectual disabilities, has focused on their participation levels [23] and regional discrepancies [24]; parents' experiences [25,26], input [27], and interactions during the IEP meeting [28]; pupils' roles [29]; and student-led IEP meetings [30]. However, this previous research has revealed a power imbalance between schools and families, which can lead to families having a diminished role in the process.…”
Section: Challenges and Collaboration In The Iep Goal-setting Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents have much greater input into the educational planning for their children, often in the form of an Individual Education Plan (IEP), which is a collaborative document detailing the key goals and objectives to be met by the child. As parents have significant knowledge of their children's abilities and needs, they are logical and necessary partners in the educational process [50]. Parents also have heightened knowledge of process and procedures involved in the schooling system and their rights in relation to the Disability Discrimination Act [23] and Disability Standards for Education [27], due to the increased access to online information.…”
Section: Timeframe-mid-2000s To End Of 2020mentioning
confidence: 99%
“…The IEP process provides broad authority to parents involved in the identification of autism and the subsequent creation of the program tailored to the educational needs of each child (Ruble et al, 2010). The complexities of navigating parent's rights and responsibilities under this system can be overwhelming for any parent or caregiver (Kurth et al, 2019). The complexities of the system may disproportionally impact parents whose first language is not English (e.g.…”
mentioning
confidence: 99%